Finite element model analysis of bolt overlap for angle steel connections of 5G shared transmission towers - Xu, Weizhou; Hu, Yashan; Dai, Ya; Zhang, Nan; Tong, Teng (Frontiers in Mechanical Engineering, 2025)
Introduction:The overlap strength of angle steel connection bolts significantly affects the change of node failure mode in the construction of 5G shared transmission towers, thereby affecting the bearing capacity of components. Methods:This study conducted an in-depth exploration of this issue using a finite element model, involving model construction, boundary condition setting, and material property definition, to simulate various common bolt lap strengths.Results and Discussion:It was found that the optimized angle steel connection significantly improved the bolt lap strength, with the average result reaching 7900N, much higher than the traditional 2000N (an improvement of 5800N). Subsequently, the research showed that increasing the lap strength from 100 MPa to 500 MPa did not significantly enhance the torsional bearing capacity of angle steel connections, while in the range of 500-800 MPa, the torsional bearing capacity gradually increased. For various working conditions (e.g., Y-direction working conditions and peak wind load working conditions), the optimized bolt overlap of angle steel connections performed well: the stress-strain ratio values at all positions were greater than 2.4 GPa, and the maximum displacement of bolt overlap was 8.67 mm. When the tower height was above 180m, the bearing capacities such as material strength and tower joint strength fell within the range of 17.87-19.98 MPa, and the maximum lap strength of the bolt occurred at the central axis of the bolt, approximately 2.5 MPa.Conclusion:The optimized bolt overlap of angle steel connection has significant advantages in improving material bearing capacity and ensuring structural stability and safety. This will have practical significance for the design and construction of 5G shared transmission towers, helping to improve their operational efficiency and service life.